Commissive Speech Act in Movie “Army of the Dead” 2021 - Ronaldo Samosir; Afriana Afriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The aim of this research is to find out the types of commissive speech act in movie “Army of the Dead” 2021. This research used the theory commissive speech act from Searle and Vanderveken to categorize the utterance that appeared in the data source into the types of commissive speech act. This research applied descriptive qualitative research method by Merriam as the data is in the form of words and phrases. This research used observational method from Creswell to collect the data. According to Creswell (2014), observational method is a method when the researcher observes and collect the venture of the research object. To find out the data, note-taking technique by Merriam (2009) will be used in this research. Note-taking is a method for the researcher find the data by gathering the form of words that relate to the topic. This research result shown that there are 33 data of commissive speech act in movie “Army of the Dead” 2021. Which are, 6 data of refuse, 6 data of offer, 1 data of promise, 12 data of accept, 7 data of assure and 1 data of guarantee. This result shown that the type of accept is the most used type of commissive speech act with (12 data) that used in this movie. And the type of promise and guarantee are the rarest type with (1 data) that used in this movie.